Let them shine: insights from an outdoor education initiative for primary school students about an olive tree collection - Lima, M Alexandra Abreu (Preschool and Primary Education, 2020)
Nowadays, experiential learning and outdoor education are increasingly relevant due to phenomena of ‘extinction of experience’ (Pyle, 1993), ’plant blindness’ (Wandersee & Schussler, 2001) and ‘nature deficit childhoods’ (Louv, 2005). This paper revisits experiential learning and outdoor education concepts and some of their development history for European and North American contexts. It highlights plant biodiversity as an important issue for outdoor education due to current risks of biodiversity loss/erosion within agriculture (Linos, et al., 2014; Mousavi et al., 2017). It describes an experiential learning initiative held in Portugal, in 2019, at an olive tree collection (Olea europaea L.) planted for a research project during the 1980s-1990s. The initiative was structured with outdoor visits as a complement to classroom learning. It engaged five teachers and 117 students, aged 8-9 years. Data from students and teachers questionnaires results are evaluated as a way to counteract the above phenomena and to benefit children training. Existing research indicates the role of provision of supportive and stimulating environmental conditions during childhood to strengthen individual competencies to make decisions able to accelerate transition for more sustainable societies (U.N., 2019). This paper results articulates with existing research and can be useful to inform effective outdoor programme design.